1974
DOI: 10.1073/pnas.71.6.2520
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Inhibition of the Growth of Virus-Transformed Cells in Culture by Rifazone-8 2 , a New Rifamycin Derivative

Abstract: Rifampicin, a well-known derivative of rifamycin, has been shown to inhibit the replication of vaccinia virus in tissue culture when added at very high levels (>100 ug/ml) (15,16) and to reduce the incidence of adenovirus-induced tumors in male hamsters (16). In chick cells it has been argued that rifampicin (a) inhibits focus formation by Rous sarcoma virus (RSV) (1), (b) has no effect on transformation, as it is toxic to both normal and transformed cells (17), and (c) is preferentially toxic to transformed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…PAT cells and chicken embryo fibroblasts (CEF) were prepared from 16-and 10-day-old chicken embryos, respectively, as described (4,5). Cells were infected with various strains of Rous sarcoma viruses (6,7), including a temperature-sensitive mutant virus, LA-24 (Prague, Subgroup A), with a defect in the src gene (8). Focus-forming units and infectious centers were determined according to Rubin (9).…”
mentioning
confidence: 99%
“…PAT cells and chicken embryo fibroblasts (CEF) were prepared from 16-and 10-day-old chicken embryos, respectively, as described (4,5). Cells were infected with various strains of Rous sarcoma viruses (6,7), including a temperature-sensitive mutant virus, LA-24 (Prague, Subgroup A), with a defect in the src gene (8). Focus-forming units and infectious centers were determined according to Rubin (9).…”
mentioning
confidence: 99%
“…Chicken embryo fibroblasts were prepared and cultured as described (8). Primary cultures were infected with virus (LA24) by addition of 3.5 X 106 focus-forming units to approximately 5 X 105 cells in each 100-mm culture dish.…”
Section: Methodsmentioning
confidence: 99%
“…Rifa mycin derivatives have also been shown in cell culture studies to be selectively toxic to virally-transformed chick cells [16,17] and leukemic leukocytes [18,19], and to lead to the pro duction of non-infectious progeny virus in transformed chick cells [20], In vivo experimental programs to evaluate the anti tumor potential of rifamycin derivatives have been less exten sive. Studies to date have demonstrated that Rif inhibits Wal ker 256 ascites carcinosarcoma in rats [21] and exerts a pro phylactic effect against adenovirus-induced tumors in male hamsters [22], The derivative DMB has been observed to inhi bit the onset and to decrease the total incidence of carcinogeninduced rat tumors [23].…”
Section: Introductionmentioning
confidence: 99%